The Knowledge and Therapeutic Approach of Paediatrician on Functional Constipation - Brahmantyo Ardhi Wicaksono; Fransesco B Hubert Jonathan; Agus Tini Sridevi; Dewi Friska; Badriul Hegar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Background: Functional constipation is one of the most common functional gastrointestinal disorders in children under 4 years of age. The Rome IV Criteria have standardized diagnostic criteria for functional constipation. The purpose of the study was to determine the knowledge and therapeutic approach of Indonesian pediatricians to functional constipation.Method: A cross-sectional analytic observational study with the target of 101 pediatricians practicing in the DKI Jakarta area. This study provides an electronic questionnaire which was validated with facial and construct validity and the reliability was determined by Alpha-Cronbach value.Results: The average duration of experience practicing as pediatricians was 6.83 ± 3.96 years, with a range of 5-15 years (66.3%) with the majority working in non-teaching institutions (83.2%). Pediatricians’ knowledge of functional constipation did not show a significant difference in score based on length of experience practicing as a pediatrician (p = 0.738) and place of daily practice (p = 0.690). A Significant difference was seen based on the use of Rome Criteria as a source of information on functional constipation (p = 0.047). Five to fifteen years of experience practicing and teaching hospital as place of daily practice showed a higher therapeutic approach score, although this was not statistically significant. It turned out that using Rome Criteria as a source of information does not give higher therapeutic approach scores.Conclusion: Periodic evaluation of pediatrician's knowledge and therapeutic approach is needed to maintain the quality of functional constipation care.